Comportamiento agroproductivo de tres cultivares de Glycine max (L.) Merril - Aracelis Romero-Arias; Raquel María Ruz-Reyes; Santa Laura Leyva-Rodríguez (Pastos y Forrajes, 2023)
Objective: To evaluate the agroproductive performance of three cultivars of Glycine max (L.) Merril on a loose brown soil without carbonate.